2017
DOI: 10.18632/oncotarget.18351
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum bilirubin levels and essential trace elements status in an adult population

Abstract: ObjectiveThis paper aims to evaluate the relations between serum bilirubin and essential trace elements in an adult population.ResultsDemographic and clinical data were stratified according to the median of serum bilirubin concentrations (50th percentiles). There were statistical differences in regarding with age, body mass index, white blood count, hemoglobin, mean corpuscular hemoglobin, alanine aminotransferase, creatinine, high-sensitivity C-reactive protein, iron, zinc and copper. Studying the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…In addition to the increased utilization of UA and tBILI as radical scavengers, other factors related to serum iron could also influence their levels. Serum iron was found to be independently correlated with bilirubin, and inflammation has been proposed as the basis for this relationship (28). This could be relevant to the low tBILI observed in diabetic subjects with low serum iron levels in our study, considering that T2DM is an inflammatory state (7).…”
Section: Discussionsupporting
confidence: 63%
“…In addition to the increased utilization of UA and tBILI as radical scavengers, other factors related to serum iron could also influence their levels. Serum iron was found to be independently correlated with bilirubin, and inflammation has been proposed as the basis for this relationship (28). This could be relevant to the low tBILI observed in diabetic subjects with low serum iron levels in our study, considering that T2DM is an inflammatory state (7).…”
Section: Discussionsupporting
confidence: 63%
“…Choi et al (2018) [80] summarized the evidence supporting the association between zinc deficiency and CVD development, underscoring the potential diagnostic and prognostic implications of zinc homeostasis-associated molecules in CVD. Peng & Wei (2017) [81] found that low serum zinc concentrations and high serum copper concentrations were linked to inflammatory factors in patients with CVD.…”
Section: Importance Of Zinc (Zn)mentioning
confidence: 99%
“…Both animal-derived bilirubin, such as that from cow bezoar, and plant-derived bilirubin analogs, like phycocyanin, have been shown to exert beneficial effects on human health [ 13 15 ]. Moreover, taking iron and zinc supplements or adjusting dietary strategies can gently increase bilirubin concentration [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%